Evaluation of Patient Satisfaction of an Outpatient Colonoscopy Service in an Asian Tertiary Care Hospital - Wah-Kheong Chan; Khean-Lee Goh (Gastroenterology Research and Practice)
Aim. To evaluate patient satisfaction towards an outpatient colonoscopy service and analyze areas of dissatisfaction for potential improvement. Method. Consecutive patients attending the outpatient diagnostic colonoscopy service in University of Malaya Medical Centre between 1st February and 31th July 2010 were interviewed using a questionnaire modified from the modified Group Health Association of America-9 (mGHAA-9) questionnaire. Favorable/unfavorable responses to each question, contribution of each question to unfavorable responses, and effect of waiting times on favorable/unfavorable response rates were analyzed. Results. Interview was carried out on 426 patients (52.1% men). Mean age ± standard deviation was 61.3±12.9 years old. Mean waiting times for colonoscopy appointment and on colonoscopy day were 3.8±2.7 months and 1.1±0.8 hours, respectively. The main factors that contributed to unfavorable responses were bowel preparation followed by waiting times for colonoscopy appointment and on colonoscopy day (32.3%, 27.5%, and 19.6%, resp.). Favorable responses diminished to undesirable levels when waiting times for colonoscopy appointment and on colonoscopy day exceeded 1 month and 1 hour, respectively. Conclusion. Bowel preparation and waiting times were main factors for patient dissatisfaction. Waiting times for colonoscopy appointment and on colonoscopy day should not exceed 1 month and 1 hour, respectively, to maintain acceptable levels of patient satisfaction.